2018
DOI: 10.1002/jcp.27941
|View full text |Cite
|
Sign up to set email alerts
|

Competing endogenous RNA (ceRNA) cross talk and language in ceRNA regulatory networks: A new look at hallmarks of breast cancer

Abstract: Breast cancer (BC) is the most frequently occurring malignancy in women worldwide. Despite the substantial advancement in understanding the molecular mechanisms and management of BC, it remains the leading cause of cancer death in women. One of the main reasons for this obstacle is that we have not been able to find the Achilles heel for the BC as a highly heterogeneous disease. Accumulating evidence has revealed that noncoding RNAs (ncRNAs), play key roles in the development of BC; however, the involving of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
197
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 231 publications
(201 citation statements)
references
References 213 publications
(360 reference statements)
4
197
0
Order By: Relevance
“…Subcellular fractionation assay revealed that IGFL2‐AS1 was located primarily in the cytoplasm, and scarcely in the nucleus in SGC‐7901 or BGC‐823 cells (Figure 3B), suggesting that IGFL2‐AS1 may be involved in posttranscriptional regulation of target genes. LncRNAs can function as competing endogenous RNA (ceRNA) by sponging miRNAs 27,28 . Bioinformatics analysis was performed using the online database RegRNA 2.0 (http://regrna2.mbc.nctu.edu.tw/detection.html) to identify miRNAs that interact with IGFL2‐AS1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcellular fractionation assay revealed that IGFL2‐AS1 was located primarily in the cytoplasm, and scarcely in the nucleus in SGC‐7901 or BGC‐823 cells (Figure 3B), suggesting that IGFL2‐AS1 may be involved in posttranscriptional regulation of target genes. LncRNAs can function as competing endogenous RNA (ceRNA) by sponging miRNAs 27,28 . Bioinformatics analysis was performed using the online database RegRNA 2.0 (http://regrna2.mbc.nctu.edu.tw/detection.html) to identify miRNAs that interact with IGFL2‐AS1.…”
Section: Resultsmentioning
confidence: 99%
“…LncRNAs can function as competing endogenous RNA (ceRNA) by sponging miRNAs. 27,28 Bioinformatics analysis was performed using the online database miR-4656) were predicted to interact with IGFL2-AS1. Luciferase reporter assay was then conducted to verify the interaction between the miRNAs and IGFL2-AS1.…”
Section: Igfl2-as1 Functions As a Molecular Sponge Of Mir-802mentioning
confidence: 99%
“…Particularly, adverse rules of miRNAs‐sponging lncRNAs, involved in ceRNA networks (ceRNETs), have been shown in BC . Eades discovered lincRNA‐ROR/miR‐145/ARF6 mRNA networks interacting with metastasis and prognosis in triple‐negative BC in 2015 …”
Section: Introductionmentioning
confidence: 99%
“…14 Eades discovered lincRNA-ROR/miR-145/ ARF6 mRNA networks interacting with metastasis and prognosis in triple-negative BC in 2015. 15 Long intergenic nonprotein coding RNA 520 (LINC00520) is located at human chromosome 14q22.3. LINC00520, a highly conserved long-chain noncoding RNA with a length of about 20kb, is widely expressed in various tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Although much remains to be discovered about the stoichiometry, subcellular localization, and other factors underpinning the effectiveness of ceRNA regulation, a tremendous body of literature from multiple studies has identified specific miRNA/ceRNA networks that are key players in the development of several cancers. These have been extensively reviewed elsewhere [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%